FORMULATION AND PHYSICAL CHARACTERIZATION OF A BODY SCRUB MADE FROM COFFEE GROUNDS TO ENHANCE ITS UTILITY AND PROMOTE SUSTAINABILITY - Siti Hanan; Eka Lailita Eti Varina; Mariyatul Jannah; Putri Nuraida; Muhammad Fariz; Siti Novianti; Fayyadh Annash (Yayasan Education and Social Center, 2025)
Body scrubs from natural ingredients are one of the right choices as well as can support the back to nature program. One of the natural ingredients that contains antioxidants is coffee grounds waste. This study aims to characterize the physical stability of body scrub formula with coffee grounds. The research method carried out includes two stages, namely the preparation of body scrub cream preparations and the evaluation of its physical properties. The results of the study showed that the lemon, honey, and aloe vera variants got a normal pH, namely 4-6. For the best pH, it is indicated by the aloe vera variant with a value of 5.9 to 6. The results of the skin irritation test showed that all variants of the scrub showed no signs of skin irritation after testing. This indicates that the formulation is safe to use topically. For organelliptic test results, all variations appeared normal. However, the formula still needs to be optimized for the body scrub base so that it can be tested with more detailed tests.